Learn objective-C on the Mac - Dalrymple, Mark (Apress, 2008)
"In this book, you'll find a full exploration of the Objective-C programming language, the primary language for creating Mac OS X and iPhone applications. There are goodies here for everyone, whether you're just starting out as a Mac developer or a grizzled programmer coming from another language. You'll discover all of the object-oriented purity and Smalltalk heritage coolness of Objective-C - such as instantiation, protocols for multiple inheritance, dynamic typing, and message forwarding. Along the way, you'll meet Xcode, the Mac development environment, and you'll learn about Apple's Cocoa toolkit."--Jacket